Designing Android-Based Mobile Application for Language Learning (MALL) for the National Exam Simulation - Wijayanto, Pikir Wisnu; Hernawati, Elis (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2019)
This research aims at designing an Android-based mobile application for language learning (MALL) for the final exam simulation of the English subject for junior high school students. The method used in building the Android-based mobile application is the software development life cycle (SDLC). Based on the implementation of user design and testing, the user (teacher and students) can do a test by using an application that runs on the Android platform. The Android device will request (get / post) to the server via the internet. Then the web server (PHP) will process the request from Android and will query the database. The computer then sends data to the Android device via JavaScript Object Notation (JSON). It is as an intermediary between the server and the Android application. The name of this application is SOUN that stands for â€œSoal Ujian Nasionalâ€ or the National Examination Questions. The teacher can manage the questions and see the scores that the students have achieved. While the students can practice answering the questions of English exercises independently, anytime and anywhere both online and offline. They can also see the score immediately based on the questions that they answered. They also know the solution, tricks, and tips on doing the exercises by choosing the menu provided. Therefore, the use of MALL as the learning media can become one of the alternative English learning models in order to prepare the students for practicing the simulations of the national examination